Integrating Creative Digital Content in Pesantren: Improving Santri’s Digital Literacy And Islamic Learning - Taufikin Taufikin; Sri Nurhayati; Habib Badawi; Ahmad Falah; Moh. Sholihuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Pesantren faces challenges in adapting traditional teaching methods to the development of digital technology. The digital literacy gap and limited infrastructure are the main obstacles to implementing the digitalization of learning. One solution is using creative digital content to improve learners' digital literacy and creativity. This study aims to analyze the implementation of creative digital content in learning in pesantren and assess its impact on digital literacy and creativity of students. In addition, this study also examines the main challenges of pesantren digitalization and proposes strategic solutions to ensure its effectiveness and sustainability. A qualitative approach with a case study at PPATQ Raudlatul Falah Bermi Gembong Pati Central Java was used as the research location, and the Observations were also made at four Islamic boarding schools in the Central Java region. Data were collected through interviews with Santri and Ustadz, joint observation and document analysis. The data were analyzed thematically to identify patterns in the pesantren education system. The results showed that digitization improved santri's understanding of learning materials and their memory. Santris, who actively participates in digital content creation, is more creative and has better digital skills than traditional methods. However, some challenges include inadequate teacher training and limited internet access. Therefore, strategies are needed to control and strengthen the infrastructure. This study contributes to developing digital learning models in Pesantren and provides policy recommendations for Pesantren leaders and stakeholders to support the transformation of Islamic education through technology